The Impact Of Lavender Aromatherapy Techniques And Endorphin Massage On Anxiety During The First Active Phase - Febriantini, Asri; Mamlukah, Mamlukah; Wahyuniar, Lely; Nastiti Iswarawanti, Dwi (Ann Publisher, 2024)
Stress and an overabundance of catecholamine hormones released during labor can cause smooth muscle and uterine ischemia, which heightens pain impulses. A light touch or therapeutic massage stimulating the body to release endorphin compounds can relieve pain and comfort. This type of massage is known as endorphin massage. Linalool, a compound found in lavender aromatherapy, has calming and muscle-relaxing properties. This research project aims to ascertain